Wheat Germ as Partial or Total Substitutive of Lean Meat in Low-Fat Cooked Sausages - Marta Rodríguez-Fernández; Isabel Revilla; Pablo Rodrigo; Rocío López-Calabozo; Ana María Vivar-Quintana (Foods)
Wheat germ is a byproduct of the cereal industry that contains high levels of protein, fiber, B vitamins, minerals, and other functional microcomponents. However, so far, few applications have been found in the meat industry despite the growing interest in replacing meat with vegetable proteins. Therefore, the use of wheat germ for the production of low-fat frankfurters was considered. Five different formulations were prepared: control with pork meat and the following four to achieve 25%, 50%, 75%, and 100% lean meat substitution by wheat germ. Proximal composition, color, texture, emulsion characterization, fatty acid profile, fat oxidation, and consumer acceptance were then analyzed. The results showed that the incorporation of wheat germ improved emulsion stability, decreasing significantly total expressible fluid and jelly/fat separation, although increasing the back extrusion force. In terms of the final product, the progressive substitution of meat by germ resulted in significant increases in carbohydrates, in special of fiber, and ash as well as significant decreases in moisture and total fat. Sausages made with germ were darker (L*), as well as harder, chewier, and gummier, but less cohesive and elastic. Similarly, wheat germ substitution improved the quality of the lipid profile showing higher levels of, but decreased acceptability for replacements > 25%. Substitution of meat was feasible up to 25%, a formulation for which there was hardly any significant difference with the control.